THE EFFECT OFTOFU WASTE FLOURSUBSTITUTIONON JELAWAT (Leptobarbus hoevenii)FISH CRACKERTOWARD CONSUMER ACCEPTANCE - Alvin Hadi Martha; N Ira Sari; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was aimed to determine of tofu waste flour effect on jelawatfish cracker toward consumer acceptance. The fresh catfish as raw material was obtained from Air Tiris village Kampar regency. Method used in this research was experimental method with Completely Randomized Design non factorialconsisting of 4 levels treatment i.e. KJ0 (jelawat fish cracker without tofu waste flour), KJ1(jelawat fish cracker with 50 g of tofu waste flour), KJ2(jelawat fish cracker with 100 g of tofu waste flour), KJ3(jelawat fish cracker with 150 g of tofu waste flour). The result showed that the treatment with substitution 100 gram of tofu waste flour had 80% of consumer acceptance level (65 panelists), whereas appearance (3.17) with characteristic was brownish colour, texture (3.16) with crunchy texture, aroma (2.85) with typical soybean aroma, flavor (3.43) typical soybean flavor, for moisture content 3.22%, protein content11.08%, fat content6.44%, ash content2.71% and 64% of adsorption power. Keywords : Fish cracker, jelawat fish, tofu waste flour, substitution, consumer acceptance